2014
DOI: 10.15381/rinvp.v16i2.6550
|View full text |Cite
|
Sign up to set email alerts
|

Bienestar de las mujeres lesbianas en el medio rural: un estudio exploratorio

Abstract: RESUMENLa homosexualidad, especialmente en el medio rural, ha sido relegada a un segundo plano, especialmente cuando se trata de la mujer. Este estudio tiene por objetivo aproximarse al estado de bienestar de mujeres homosexuales en el medio rural, así como conocer las relaciones entre diferentes aspectos del bienestar en esta población. Basándonos en un diseño transversal, se llevaron a cabo entrevistas semiestructuradas, así como escalas para conocer diferentes variables relacionadas con el bienestar. Los re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Although coming from rural areas has been identified as a potentially decisive factor in many areas related to health, research in other countries suggest that more specific and contextualized studies are needed (Prairie et al, 2019). However, studies conducted in Spain have identified significant barriers to small‐town dwellers (Aragó Navarro, 2019) in rural settings, particularly lesbian women (Fernández‐Rouco et al, 2013). There is also research highlighting socio‐spatial precariousness as a result of the oppressive coexistence experienced by many LGBTI people (Ugidos et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Although coming from rural areas has been identified as a potentially decisive factor in many areas related to health, research in other countries suggest that more specific and contextualized studies are needed (Prairie et al, 2019). However, studies conducted in Spain have identified significant barriers to small‐town dwellers (Aragó Navarro, 2019) in rural settings, particularly lesbian women (Fernández‐Rouco et al, 2013). There is also research highlighting socio‐spatial precariousness as a result of the oppressive coexistence experienced by many LGBTI people (Ugidos et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Family rejection may be particularly harmful if it is reinforced by a conservative kinship-oriented social environment. Although urban Spain may offer support for sexual minorities, rural communities remain patriarchal, conservative and religiously fundamental, and strongly enforce adherence to traditional gender roles, especially in families (Ferna´ndez-Rouco et al, 2013;Moses and Buchner, 1980). Thus in this study we hypothesize that higher levels of alienation from family (i.e.…”
Section: Interpersonal Needsmentioning
confidence: 99%